• Выполните умножение:
    (б-4)(б^2+4b+16)
    (2а+3б)(4а^2-6аб+9б^2)
    (x^3+6у^2)(х^6-6x^3 у^2+36y^4)

Ответы 1

  • (b - 4)(b² + 4b + 16) = b³ - 4b² + 4b² - 16b + 16b - 64 = b³ - 64

    (2a + 3b)(4a² - 6ab + 9b²) = 8a³ + 12ba² - 12ba² - 18ab² + 18ab² + 27b³ =    = 8a³ + 27b³

    (x³ + 6y²)(x⁶ - 6x³y² + 36y⁴) = x⁹ + 6y²x⁶ - 6x⁶y² - 36x³y⁴ +

    + 36x³y⁴ + 216y⁶ = x⁹ + 216y⁶

    • Автор:

      tobiepacs
    • 4 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years